Volition and motivations influence on weight maintenance. Issue 2 (3rd April 2019) - Elsborg, Peter; Nielsen, Johan Bundgaard; Pfister, Gertrud Ursula; Dümer, Vivian; Jacobsen, Anette; Elbe, Anne-Marie
Abstract : Purpose: The purpose of this paper is to explore how the psychological constructs volition and motivation influence successful and unsuccessful weight maintainers' experiences during the difficult period following an intensive lifestyle intervention. Design/methodology/approach: Post lifestyle intervention semi-structured interviews with 11 successful and four unsuccessful weight maintainers were conducted. Findings: The eight themes that emerged and the differences between successful and unsuccessful maintainers were theoretically explained applying the self-determination theory (motivation) and the personal systems interaction (volition). Practical implications: The study validates and coheres with previous findings on the importance of self-regulation and autonomous motivation for weight loss maintenance. Additionally, the study's findings expand the literature by explaining both empirically and theoretically how the quality of motivation concerning an activity influences the level of volitional intensity needed when wanting to either engage in goal oriented or refrain from goal opposing activities. Originality/value: Developing effective obesity interventions has become essential, as obesity is a growing health threat in most countries in the world. However, there is a gap in the literature with regards to qualitative psychological studies with a clear theoretical framework informing intervention development.